Glutamine Deprivation Promotes the Generation and Mobilization of MDSCs by Enhancing Expression of G-CSF and GM-CSF - Sun, Hong-Wei; Wu, Wen-Chao; Chen, Hai-Tian; Xu, Yi-Tuo; Yang, Yan-Yan; Chen, Jing; Yu, Xing-Juan; Wang, Zilian; Shuang, Ze-Yu; Zheng, Limin (Frontiers in Immunology, 2021)
Solid tumors are often challenged by hypoxic and nutrient-deprived tumor microenvironments (TME) as tumors progress, due to limited perfusion and rapid nutrient consumption. While cancer cells can demonstrate the ability to survive in nutrient-deprived conditions through multiple intrinsic alterations, it is poorly understood how nutrient-deprived cancer cells co-opt the TME to promote cancer cell survival and tumor progression. In the present study, we found that glutamine deprivation markedly potentiated the expression of G-CSF and GM-CSF in mouse mammary cancer cells. The IRE1α-JNK pathway, which is activated by glutamine starvation, was found to be important for the upregulation of these cytokines. G-CSF and GM-CSF are well-known facilitators of myelopoiesis and mobilization of hematopoietic progenitor cells (HPC). Consistently, as tumors progressed, we found that several myeloid HPC compartments were gradually decreased in the bone marrow but were significantly increased in the spleen. Mechanistically, the HPC-maintaining capacity of the bone marrow was significantly impaired in tumor-bearing mice, with lower expression of HPC maintaining genes (i.e. CXCL12, SCF, ANGPT1, and VCAM1), and reduced levels of mesenchymal stem cells and CXCL12-producing cells. Furthermore, the mobilized HPCs that displayed the capacity for myelopoiesis were also found to accumulate in tumor tissue. Tumor-infiltrating HPCs were highly proliferative and served as important sources of immunosuppressive myeloid-derived suppressor cells (MDSCs) in the TME. Our work has identified an important role for glutamine starvation in regulating the expression of G-CSF and GM-CSF, and in facilitating the generation of immunosuppressive MDSCs in breast cancer.